Role of IL-10 in hepatocyte tight junction alteration in mouse model of experimental colitis. - Mazzon, Emanuela (2002)
BACKGROUND: A variety of hepatobiliary abnormalities have been described in patients with chronic inflammatory bowel diseases (IBDs). The purpose of this study was to investigate the role of endogenous IL-10 in alteration of hepatocyte TJ paracellular barrier and in the rapid transcytotic vesicular pathway modification associated with intestinal inflammation. MATERIALS AND METHODS: To address this question, we used an experimental model of colitis, induced by dinitrobenzene sulfonic acid (DNBS). When compared to DNBS-treated IL-10 wild-type (IL-10WT) mice, DNBS-treated IL-10 knock-out mice (IL-10KO) mice experienced a higher rate of the extent and severity of the histological signs of colon injury. RESULTS: Colon and liver levels of the pro-inflammatory cytokines tumour necrosis factor, interleukin-1 beta and interleukin-6 were also greatly enhanced in IL-10KO mice in comparison to wild-type mice. Liver histology from IL-10KO and IL-10WT did not show any parenchymal and portal tract inflammation at 4 days after DNBS administration. Serum total bilirubin and Alanine aminotransferase, were significantly increased in DNBS-IL-10KO mice vs. DNBS-IL-10KO mice. Therefore, we found an increase of tight junctional permeability to lanthanum nitrate (molecular weight, 433) in the livers from DNBS-treated IL-10WT mice; lanthanum accumulated throughout the junctional area up to the most apical region bordering the lumen. Absence of a functional IL-10 gene in IL-10KO mice resulted in a significant augmentation of apical diffusion of lanthanum after DNBS-induced colitis. Immunofluorescent labelling of frozen liver sections from DNBS-IL10KO mice, immunolocalization for and claudin-1 and ZO-1 resulted in a significant alteration in the localization of the immunosignals for claudin-1 and ZO-1 after DNBS administration in comparison with DNBS-IL10WT. CONCLUSION: In conclusion, we suggest that the absence of IL-10 may represent an important pathophysiological mechanism of hepatobiliary injuries and cholestasis observed in patients with IBD.